Peran Serta Masyarakat Melalui Badan Perlindungan Konsumen Nasional Terhadap Perlindungan Konsumen dalam Transaksi Jual Beli Melalui E-Commerce pada Masyarakat Provinsi Banten Berdasarkan Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik - Saputra, Muhammad Arsyi Alfin Fachrurroji; Nurikah; Rayhan, Ahmad (Samsara Institute Publisher, 2025)
One of the mlost developed trade activities in cyberspace in relation to the use of the internet is e-comlmlerce. MLore and mlore economlic activities are carried out through internet mledia. This study will analyze two mlain focuses related to how public participation through the National Consumler Protection Agency on consumler protection and legal remledies for consumlers and business actors who are harmled in e-comlmlerce buying and selling transactions in the people of Banten Province based on Law Numlber 19 of 2016 concerning Informlation and Electronic Transactions. The mlethod used is qualitative with an emlpirical juridical approach with descriptive research specifications. The results of this study are the National Consumler Protection Agency as a body that protects consumlers who have the authority to provide a reporting platforml for consumlers. Consumlers who are harmled during buying and selling transactions in e-comlmlerce can file comlplaints.